Dendritic cell targeting in cultured fish in Argentina for vaccine development - Ghersa, Federica; Soria, Ivana; Quattrocchi, Valeria; Gammella, Mariela; Langellotti, Cecilia Ana; Zamorano, Patricia Ines; Rauque, Carlos Alejandro; Pappalardo, Juan Sebastián (Edición del Autor, 2019)
Premio al mejor Poster presentado en la Asociación Argentina de Nanomedicinas